Stories of war and restitution Curating the narratives of the !xun storyteller Kapilolo Mahongo (1952 – 2018) - Winberg, Marlien (Department of Archaeology, 2021)
Southern Africa's San people have embodied the sub-human other in colonial and Apartheid historiography and has lived fractured, often traumatised lives as a result. The aftermath of dispossession, genocide and war has echoed down the generations and still manifests itself in visible and intangible ways. Previous research has not addressed the personal stories of the immigrant !xun community living on the San farm, Platfontein, near Kimberley in the Northern Cape Province. My thesis works towards filling this gap. The focus of my research was to open up a space in which the !xun leader and storyteller, Kapilolo Mario Mahongo, could actively engage the energy of storytelling in representing his personal history and for the first time, record an Indigenous !xun perspective of the regional wars during the latter part of the 20th century - and its aftermath. By focusing on his personal stories, I demonstrate how anti-colonial narratives are embodied in specific and multiple histories and cannot be collapsed into homogenized narratives. Kapilolo Mahongo died at the age of 68, on May 12th 2018 while working with me on curating his own and his community's stories. My thesis thus evolved to question his place in the San corpus, asking how his memoirs, and the ways in which we produced it over a period of more than twenty years, may contribute toward our knowledge – not only of his personal life, but of the !xun community's history and southern Africa's San people as a whole. With our colonial and apartheid background of discrimination, my role as fellow storyteller and researcher assumes a compelling resonance. I address this directly by engaging an autoethnographic voice to tell my story parallel to the stories by Mahongo and other !xun storytellers, with the intention of creating a record of coming together against the background of our otherness, showing how we lived our difference (through the methodology of storytelling), to create new narratives of truth. My findings report on how storytelling in indigenous epistemologies are knowledge producing and disruptive of colonial narratives, while supporting recovery from the posttraumatic effects of dispossession and war among indigenous communities.